The oral microbiome in an ecological perspective - Egija Zaura (Frontiers Research Topics, 2015)
The oral cavity harbors an immense diversity of microorganisms, including bacteria, fungi, archaea, protozoa and viruses. At health, oral microbial community is thought to be in a state of homeostasis, even after numerous perturbations (e.g., toothbrushing, food intake) a day. The breach in this homeostasis can occur for instance if the perturbations become too excessive (e.g., frequent carbohydrate intake leading to acidification of the community) or the host is compromised (e.g., inadequate immune response resulting in persistent inflammation of periodontal tissue). Aggressive antimicrobial therapy (e.g., antibiotics in case of periodontal disease or preventive antibiotic therapy before and after dental extractions) is commonly applied with all the negative consequences of this approach. So far little is known on the interplay between the environmental, host and microbial factors in maintaining an ecological balance. What are the prerequisites for a healthy oral ecosystem? Can we restore an unbalanced oral microbiome? How stable is the oral microbiome through time and how robust it is to external perturbations? Gaining new insights in the ecological factors sustaining oral health will lead to conceptually new therapies and preventive programs. Recent advances in high throughput technologies have brought microbiology as a science to a new era, allowing an open-ended approach instead of focusing on few opportunistic pathogens. With this topic we would like to integrate the current high-throughput 'omics' tools such as metagenomics, metatranscriptomics, metaproteomics or metabolomics with biochemical, physiological, genetic or clinical parameters within the oral microbial ecosystem. We aim to address questions underlying the regulation of the ecological balance in the oral cavity by including the following areas: • Ecology of oral microbiome at health • Ecology of oral microbiome under oral diseases • Ecology of oral microbiome during non-oral diseases • Shifts in the oral microbiome by therapeutic approaches (e.g., antimicrobials, replacement therapy, pre- and probiotics) • Modeling of oral ecological shifts (e.g., animal models, in vitro microcosm models) • Complex inter- and intra-kingdom interactions (e.g., bacterial-fungal-host) related to oral ecology • Environmental (e.g., diet, tobacco), host-related (e.g., immune response, saliva composition and flow) and biotic (e.g., bacterial competition) factors influencing oral ecology • Geographic variation in oral microbial ecology and diversity